Vocal Nodule and Polyp by Microlaryngoscopy and Cold Instruments - Ganesh M. Vihapure1, Abhay D. Havle2 , Mannuru Khaleel Basha3 , Naman Pincha3 , Tripti3 , Sanket C P (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim and Objective: To evaluate the usefulness of voice handicap index and seventy degree endoscopy for assessment of speech. Materials and Method: The study was conducted in the department of Otorhinolaryngolgy,tertiary care hospital,between 2018 to 2019. Results: Total of 42 cases underwent micro laryngeal surgerywithout any complications.voice Handicap index (VHI) and 70 degree scopy assessed after 10days, 1st month and 3rd month interval .All cases improved voice on 10th day and symptoms were gradually decreased. Before surgery mean was 82.43 changed to 17.31 on 10th day to 1.45 on 3rd month follow up.p value <0.005 Conclusion: Early diagnosis is important to rule out malignant changes in cases with hoarseness of voice and early treatment with microlarynoscopy is very effective shows significant improvement on voice handicap index and endoscopy and with patients satisfaction.